2003
DOI: 10.3748/wjg.v9.i5.993
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B and C markers among refugees in Athens

Abstract: It can be concluded that refugees living in Athens are an immigrant population characterized by a high incidence of HBV infection. The prevalence of HBV markers is higher among refugees from Albania and Asia. It is therefore believed that the adherence to general precautions and the initiation of HBV vaccination programs will be necessary in the future, especially in these communities. Although the prevalence of HCV infection seems to be relatively low, extended epidemiological surveys are needed to provide va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
2
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 16 publications
3
25
2
6
Order By: Relevance
“…In our study, the prevalence of hepatitis B was most common in asylum seekers from the Balkans. Roussos et al found a similar result in their study on the prevalence of hepatitis B and C markers among refugees in Athens [25]. They screened 130 asylum seekers for hepatitis B and C and found a prevalence of anti-HBsAG of 15.4% in Balkan asylum seekers, a figure that is remarkably higher than in our study [25].…”
Section: Discussionsupporting
confidence: 87%
“…In our study, the prevalence of hepatitis B was most common in asylum seekers from the Balkans. Roussos et al found a similar result in their study on the prevalence of hepatitis B and C markers among refugees in Athens [25]. They screened 130 asylum seekers for hepatitis B and C and found a prevalence of anti-HBsAG of 15.4% in Balkan asylum seekers, a figure that is remarkably higher than in our study [25].…”
Section: Discussionsupporting
confidence: 87%
“…In fact, immigrants were found to represent an important reservoir of newly diagnosed chronic HBV patients with their proportion in our chronic HBV patients increasing from the first to the second period of our study (from 30.5 to 39.7%, P = 0.046). The majority of these immigrants were from Albania, which is a country of high HBV endemicity [13][14][15]. However, the proportion of Albanians among immigrants with chronic HBV infection declined from the first to the second period of our study (from 82 to 64.5%, P = 0.027), while the relative proportion of immigrants from other countries (such as ex-USSR and Asian) increased.…”
Section: Discussioncontrasting
confidence: 61%
“…Historically, these patients have been attended to in the Unit of Tropical Medicine and International Health ''Drassanes'' located in the same district of the city. Global HBV infection in our sample reaches a value similar (18.11%) to that described in comparable patients in Sweden 17 but considerably lower than that reported in referral units of Spain 16,18 (44.8%-63.1%), Greece 19 (53.1%), and Italy 20 (38.9%). The underrepresentation of sub-Saharan African patients in this study may account for such differences.…”
Section: Discussionmentioning
confidence: 69%